How does disruptive innovation influence the funding decisions of different venture capital investors? An empirical analysis on the role of startups' communication. Issue 2 (April 2023) - Piazza, Mariangela; Mazzola, Erica; Perrone, Giovanni; Vanhaverbeke, Wim
Abstract: Entrepreneurs present their ideas in a favorable light through compelling communications that may shape the investors' impressions about the value of the startup's technology and its potential to disrupt. Assessing such communications, venture capital (VC) investors get an impression of the startup's technology and shape their willingness to commit resources to it. Since diverse kinds of VC investors pursue alternative investment objectives, they may develop different impressions of the startup's technology and accordingly make different resource commitment decisions. This paper aims to investigate the resource commitment decisions of VC investors when financing startups communicating disruptiveness by distinguishing between independent venture capitalists (IVC) and corporate venture capitalists (CVC). Analyzing data about 664 medical device and biotech startups in a 10-year period, we found that communicating disruptiveness decreases the amount of funding committed by IVC, while it has a curvilinear effect on the amount of funding provided by CVC. Our findings contribute to the literature and provide important implications for managers of startups aiming to secure funding from different VC investors.